Ophthalmic formulation of methotrexate: a strategy of using the self-assembled LacAC4A nanoparticles for non-invasive drug delivery to the ocular posterior segment - Xiao-Yun Hou; Xiao-Ling Zhang; An-Kang Ying; Yu-Xin Yue; Tao Yang; Dong-Sheng Guo; Zhi-Qing Li (Drug Delivery)
Drug delivery to ocular posterior segment remains difficult due to the challenges imposed by dynamic and static ocular barriers, lesion point targeting, and off-target effect. In this study, a novel approach is demonstrated for non-invasive drug delivery to the ocular posterior segments using lactose-modified azocalix[4] arene (LacAC4A) as a supramolecular ocular drug delivery platform. LacAC4A contains azo groups and is covalently modified by lactose groups, which confers active targeting to the retina, and induces a hypoxic response. The immunomodulator methotrexate (MTX), which is commonly used in ophthalmology to treat immune system diseases such as uveitis, was also selected as a guest to prepare MTX@LacAC4A. The prepared LacAC4A and MTX@LacAC4A systems were characterized, then the internalization mechanisms and hypoxia response abilities were determined through flow cytometry and fluorescence imaging, respectively. Besides, the delivery route and efficiency were verified, and the safety profile of MTX@LacAC4A was evaluated in multiple dimensions. Importantly, it was found that the prepared MTX@LacAC4A exhibits good biocompatibility, can effectively reach the posterior segment, and demonstrates potential ophthalmic applications. These findings lay the grounds for the future development of non-invasive ocular posterior segment disease treatments based on the advanced use of LacAC4A as a drug delivery platform.